Estudio de mercado para la creación de un operador turístico del cantón Ventanas - Lucio Cruz, Ginger Anabel (2022)
The present case study focuses on the market study for the creation of a tour operator in the Cantón Ventanas, for this purpose it was developed under the mixed, descriptive and field research methodologies seeking as a result to determine if the operator is feasible, However, with the application of qualitative and quantitative techniques, it is intended to obtain results based on the preferences, needs and requirements of the Ventanas community in the hiring of tourist service agencies. In this case, the chi-square formula was chosen. in order to calculate a part of the population to be studied, giving 381 people as a sample. Wondering how the market study affects and how, through the definitions of the variables, they guide the study in the search for follow-up in the environment against supply, demand and competition, also indicating the business opportunity in relation to the aforementioned that could be developed and the great impact for the community in front of the tourist activities that could be carried out, finally, it seeks to study the market to establish the tour operator and also contribute to the promotion of local attractions in the area as well as throughout the country.